In light of Africa : globalizing blackness in northeast Brazil - Dawson, Allan Charles, 1973- (Anthropological horizons., 2014)
In Light of Africa explores how the idea of Africa as a real place, an imagined homeland, and a metaphor for Black identity is used in the cultural politics of the Brazilian state of Bahia.